Penguatan Kompetensi Guru melalui Pelatihan Pengembangan Bahan Ajar dan Media Pembelajaran Berbasis Artificial Intelligence (AI) - Immanuel Doclas Belmondo Silitonga; Partohap S. R. Sihombing; Jumaria Sirait; Marlina Agkris Tambunan; Berliana Sihombing (Forum Kerjasama Pendidikan Tinggi, 2026)
The implementation of the Merdeka Curriculum requires teachers to possess the competence to develop innovative teaching materials and instructional media while effectively integrating digital technologies, including Artificial Intelligence (AI), into the learning process. However, a needs analysis conducted at SMP Negeri 6 Pematangsiantar revealed that most teachers had limited knowledge and skills in utilizing AI to develop instructional materials and learning media. This Community Service Program aimed to strengthen teachers' competencies through training on the development of AI-based teaching materials and instructional media to support the implementation of the Merdeka Curriculum. The program employed a participatory approach consisting of needs analysis, theoretical sessions, AI application demonstrations, hands-on workshops, mentoring, product presentations, and evaluation. The training involved 35 teachers from various subject areas at SMP Negeri 6 Pematangsiantar. The results demonstrated that all participants successfully developed instructional products, including teaching modules, handouts, student worksheets, interactive presentation media, and AI-assisted digital learning media. The developed products achieved an average quality score of 91.60, categorized as Excellent, while teachers' competency scores increased from an average pre-test score of 69.50 to a post-test score of 90.50, representing an improvement of 21.00 points. Participants' responses to the training were also highly positive, with an average satisfaction score of 4.85 (97.0%), indicating excellent acceptance of the program. These findings suggest that AI-based training integrating theoretical instruction, practical workshops, and intensive mentoring effectively enhances teachers' competencies in developing teaching materials and instructional media. The novelty of this program lies in its product-oriented training model, which integrates generative AI into the development of teaching materials and instructional media, enabling teachers to produce classroom-ready learning resources that support the effective implementation of the Merdeka Curriculum.